How Teachers Implement Online Physical Education Learning during Covid-19 Pandemic - Lubay, Lukmannul Haqim; Shavira, Annisa; Putri, Wulandari (Universitas Pendidikan Indonesia, 2021)
Various obstacles caused by the COVID-19 pandemic occur in different sectors, including in education where teachers are challenged to carry out different learning forms to achieve learning objectives. Therefore, a study on the implementation of online Physical Education learning, especially to find out whether the implementation is relevant to the learning objective achievement or not, is essential. For this reason, this study was aimed at finding out how the teachers implemented Physical Education online learning during COVID-19 pandemic. The samples of this research were 15 Physical Education, Sports, and Health teachers at Public Elementary Schools in Bandung City. The survey method was carried out by distributing questionnaires in digital form to each teacher with the help of Google Forms. The analysis of this study was administered using a univariate descriptive analysis to explain each sub-indicator. The findings showed that the teachers prepared the Lesson Plan and delivered learning activities based on the Lesson Plan, even though the learning process was carried out online. The scope of learning materials and motivation were conveyed by the majority of the teachers. Furthermore, almost every teacher provided feedback and assignments to students. The assessment was also considered important and carried out by the teachers.